Sufi Education Efforts in the Development of Modern Psychology - Badri, Khairul Nizam Bin Zainal; Andi, Hari Krishnan (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
Modern psychology tends to study human development in a negative way; whereas the scope of research in positive human development should be taken into account. For the purpose of psychological development, the field of Sufi education needs to be considered. The four most important subjects in Sufi education are faith, worship, customs and virtue, all four of which are key factors in the purification of the soul. In modern times, human life tends to be based on the philosophy of socio-capitalism; which has made the human lifestyle increasingly materialistic-hedonistic. As a result, crime and mental illness increase. Sufi education appears to be very relevant in addressing issues of material progress and social relations. This is because humans as unique beings need not only material things, but spirituality as well where both require balance. Through commitment and the Sufi exercises, the human potential is able to move towards positive instead of negative. But one thing to note for further study is the self-disclosure (tajalli) process in Sufi thought; which is very abstract at its height. Therefore, the measure of knowing the level of happiness is very speculative. Qualitative research is needed to determine the appropriate size.